+0

# Given are the quadratic functions f(x) = -2x 2 + 4x - 2 and g(x) = x 2 - 2x + 3 . Also is given the family of lines y = -2x + p

0
216
3

Given are the quadratic functions f(x) = -2x2 + 4x - 2 and g(x) = x2 - 2x + 3. Also is given the family of lines y = -2x + p

a. At p = 0,5 there is one of the lines. This line cuts the graph of f in two points. Calculate the x coordinates of those two points of intersections.

b. There is a line  that touches the graph of f. Calculate for which value of p the line touches the graph of f.

c. Calculate for which values of p the line has two points of intersection with the graph of g.

Jun 8, 2019

#1
+2

Given are the quadratic functions f(x) = -2x2 + 4x - 2 and g(x) = x2 - 2x + 3. Also is given the family of lines y = -2x + p

a. At p = 0,5 there is one of the lines. This line cuts the graph of f in two points. Calculate the x coordinates of those two points of intersections.

So we have

y = -2x + .5        and     y  = -2x^2 + 4x - 2

Put the first function into the second for y   and we have that

-2x + .5  = -2x^2 + 4x - 2       rearrange as

2x^2 -6x + 2.5  = 0

2x^2 -6x + 5/2  = 0      multiply through by 2

4x^2 - 12x + 5  =  0   factor

(2x - 1) ( 2x - 5)  = 0

Set each factor to 0   and solve for x

2x -1  =0       2x - 5  = 0

2x = 1           2x  = 5

x = 1/2            x = 5/2 = 2.5   Jun 8, 2019
#2
+2

b. There is a line  that touches the graph of f. Calculate for which value of p the line touches the graph of f.

y = -2x + p        and     y  = -2x^2 + 4x - 2      set these equal

-2x + p  = -2x^2 + 4x - 2     rearrange as

2x^2  -6x + (2 + p)  = 0

If the line just touches the quadratic.....then the discriminant must   =  0

So we have that

(-6)^2 - 4(2)(2 + p) = 0

36 - 8(2 + p)  = 0

36 - 16 - 8p  = 0

20 -8p  =0

20 = 8p       divide both sides by 8

20/8  = p   =  5/2

See the graph here :  https://www.desmos.com/calculator/cxek0jmo32   Jun 8, 2019
#3
+2

c. Calculate for which values of p the line has two points of intersection with the graph of g.

y = 2x + p      y  = x^2 - 2x  + 3

x^2 - 2x + 3  =  2x + p     rearrange   as

x^2 - 4x + (3 - p)  = 0

If the discriminant is  >  0....we will have two intersection points so

(-4)^2  - 4(3 -p)  > 0

16 - 12 + 4p  > 0

4 + 4p > 0

1 + p > 0

p > -1   Jun 8, 2019